Risk Factors for Combat-related PTSD Case Studies of Filipino Active Duty Soldiers. [article]. - Fajarito, C.
Military personnel have been consistently exposed to adverse potentially traumatic events (PTEs) leading to a higher risk of acquiring posttraumatic stress disorder (PTSD). Although PTSD is incurred following a traumatic event, not all will have PTSD. Hence, risk factors that make one vulnerable towards PTSD development are noteworthy for investigation. Additionally, more studies are needed to examine PTEs?' role in PTSD development. This study contributes to the paucity of research on Filipino soldiers. It aimed to investigate PTE risk factors for combat-related PTSD as experienced by three Filipino active duty combat soldiers diagnosed with PTSD. Data triangulation and convergence were classified according to these PTE risk factor categories: combat-related experiences, precombat and postcombat experiences at work, and nonmilitary experiences. Recommendations are made for the prevention of the development of PTSD among active duty military personnel.
Keywords: Risk factors; Potentially traumatic events (PTEs).; Combat-related PTSD; Soldiers; Military Personnel